Authorities of Preparation and Hospitality of Applications for Post-Conditions Post-Decision of Constitutional Court - Nur Basuki Minarno (Universitas Airlangga, 2019)
The objective of Pre-Trial is basically to provide justice rights protection from abuse of power and the arbitrary actions of law enforcement officers. Pre-Trial is as the guard for the realization of due process of law. Hence, its authority is not limited to Article 77 of the Criminal Law Procedural Code and the decision of Constitutional Court No.21/PUU-XII/2014. The dismissal of Pre-Trial appeal as provided for in article 82 paragraph (1) sub-paragraph d of the Criminal Law Procedural Code and the decision of the Constitutional Court No.102/PUU-XII/2015 do not have a sufficient rational basis. Pre-Trial and principal case examination should not terminate each other. Conversely, the result of Pre-Trial will be used as a reference to analyze whether evidence used in the principal case examination is conducted properly or not. Thus, when a Pre-Trial examination is underway, the chief of a judge of the district court must adjourn the principal review of his case.